Analysis of The Implementation on Community Empowerment Policies in Denpasar, Bali, Indonesia - Junaedy, I Kadek Dede; I Made Sumada; Azhari Aziz Samudra (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2024)
This research aimed at understanding the implementation concerning the Denpasar Municipality government policy which is called “Kube